2019
DOI: 10.1080/13621718.2019.1586162
|View full text |Cite
|
Sign up to set email alerts
|

Functionally graded structures of refractory metals by wire arc additive manufacturing

Abstract: Functionally graded components are usually preferred for severe and critical service conditions, thanks to the possibility of achieving different complimentary material properties within the same structure. Wire + Arc Additive Manufacturing is an emerging technology which lends itself well to the production of sound graded structures. In this study, an integral structure of two functional gradients, namely tantalum to molybdenum, and molybdenum to tungsten, was successfully deposited. A linear gradient was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…It can be seen from the equation that the total value of J consists of an elastic and a plastic term, which are calculated using Equations ( 5) and ( 6), respectively. In these equations, K is the stress-intensity factor, which varies for different specimen geometries [29]; ν is the Poisson's ratio; a 0 is the initial crack length; A p is the plastic area under the load vs. LLD curve; and η is a geometry-dependent function, the solution of which, for the C (T) specimen geometry, is demonstrated in Equation (7).…”
Section: Crack Length Estimation and J-parameter Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen from the equation that the total value of J consists of an elastic and a plastic term, which are calculated using Equations ( 5) and ( 6), respectively. In these equations, K is the stress-intensity factor, which varies for different specimen geometries [29]; ν is the Poisson's ratio; a 0 is the initial crack length; A p is the plastic area under the load vs. LLD curve; and η is a geometry-dependent function, the solution of which, for the C (T) specimen geometry, is demonstrated in Equation (7).…”
Section: Crack Length Estimation and J-parameter Calculationmentioning
confidence: 99%
“…The new wire-arc additive manufacturing (WAAM) technique offers a variety of benefits for various industries. Compared with other additive manufacturing (AM) techniques, such as powder-based methods, WAAM is known for lower manufacturing costs and high deposition rates for large-scale structural fabrication, which leads to reduction in manufacturing lead time [4][5][6][7]. Nevertheless, this process consists of a pure welding mechanism, depositing one metal layer on top of another while constantly reheating and cooling down the built part.…”
Section: Introductionmentioning
confidence: 99%
“…Automotive [11], Marine [115], Tools and molds [116] Nickel alloy [75] [ 117] [102,118] Inconel 718 [119], Inconel 625 [120] Aerospace [121], corrosion resistance [122], high temperature [123] Refractories [124] Tungsten [49], Molybdenum [124], Tantalum [124] Nuclear , Heat exchanger [124] Other CuSi3 [125], Bronze [126], Invar [116], Shape memory alloy [127] In summary, it has been observed that, in most of the research, a straight wall has been fabricated using WAAM and samples have been taken out from it to carry out the microstructural analysis and mechanical tests to determine its mechanical properties such as tensile strength, hardness, toughness, etc.…”
Section: Dissimilar Alloymentioning
confidence: 99%
“…The WAAM process has successfully produced large-scale parts in stainless steel [8], Inconel ® [9], titanium [10], aluminium [11] and tungsten [12]. Furthermore, functionally graded structures of refractory metals have also been deposited using WAAM [13]. The manufacture of large and engineered components by WAAM is attractive also because of the low system and operating costs, as well as the modularity of the system design [6,14].…”
Section: Introductionmentioning
confidence: 99%